Comparative analysis of rainfall event characteristics and rainfall erosivity between two experimental plots in Austria and Slovenia - Borbala Szeles; Juraj Parajka; Mojca Šraj; Günter Blöschl; Dušan Marjanović; Nejc Bezak; Klaudija Lebar; Andrej Vidmar; Peter Strauss; Carmen Krammer; Elmar Schmaltz; Patrick Hogan; et al. (Journal of Hydrology: Regional Studies)
Study region: This study investigated rainfall at two locations in the Danube Basin, the Hydrological Open Air Laboratory (HOAL) agricultural catchment in Petzenkirchen, Austria and an urban experimental plot in Ljubljana, Slovenia. Study focus: The variability of rainfall characteristics and rainfall erosivity were explored using measurements of precipitation and drop size distributions in the period 2014–2018. Annual and seasonal rainfall event characteristics were analyzed for each site and comparatively assessed using hierarchical clustering. Annual and seasonal variability of rainfall erosivity was compared between the plots. New hydrological insights for the region: Despite having the same Köppen-Geiger climate classification, differences were found between the sites. The long-term average annual precipitation in Ljubljana was almost twice as high as in the HOAL. According to the clustering analysis, larger and more intense rainfall events occurred in Ljubljana than in the HOAL. The average drop sizes and velocities tended to be lower in Ljubljana but the range of drop size distributions was larger in Ljubljana than in the HOAL. The seasonalities of rainfall event characteristics and rainfall erosivity were similar at the sites. Rainfall intensities tended to peak in summer when rainfall durations were shorter, and larger and faster drops were observed. Rainfall erosivity was between 2 and 7 times larger in Ljubljana than in the HOAL because of the more intense rainfall and single faster and larger drops during events.